Electing Madam Vice President: When Women Run Women Win - Gutgold, Nichola D. (Lexington Books, 2021)
Electing Madam Vice President presents the presidential bids of the six women who ran for the Democratic nomination for President of the United States in 2020 and the historic, groundbreaking vice-presidential candidacy of Kamala Harris.When Vice President Kamala Harris and her family moved into Number One Observatory Circle, the official Vice Presidential residence of the United States, she claimed a title no other women in the United States ever had: Vice President. She is closer to the United States presidency than any woman in history. Yet, she has repeated often that she is standing on the shoulders of women who have come before her to try to break down barriers, including the United States Presidency. Often left off the history pages, and out of many Americans’ minds, are the bids of women who run for president. The 2020 Democratic primary included the most women ever to run in one election. This book demonstrates the progress women candidates have made as they have moved from symbolic to viable candidates and shines a light on the diminishing obstacles that face women candidates while taking readers on a journey through the victorious progress of a woman United States Vice President.